2013
DOI: 10.1016/j.jtcvs.2012.09.101
|View full text |Cite
|
Sign up to set email alerts
|

Blood transfusion determines postoperative morbidity in pediatric cardiac surgery applying a comprehensive blood-sparing approach

Abstract: The incidence and volume of blood transfusion markedly affects postoperative morbidity in pediatric cardiac surgery. These results, although obtained by retrospective analysis, might stimulate attending physicians to establish stringent blood-sparing approaches in their institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 24 publications
1
49
0
2
Order By: Relevance
“…This decrease in operating room transfusion did not shift the transfusion burden to the ICU, because there was a concomitant 41% decrease in RBC transfusion during the first 12 hours after PICU admission [33]. Similarly, Redlin and colleagues [34] recently suggested a comprehensive intraoperative blood-sparing approach that resulted in no transfusion in 25% of children undergoing cardiac operations. Compared with children who received a transfusion during the postoperative period, and a fortiori to those who received a transfusion intraoperatively, these patients had a shorter length of postoperative mechanical ventilation and a shorter PICU stay [34].…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease in operating room transfusion did not shift the transfusion burden to the ICU, because there was a concomitant 41% decrease in RBC transfusion during the first 12 hours after PICU admission [33]. Similarly, Redlin and colleagues [34] recently suggested a comprehensive intraoperative blood-sparing approach that resulted in no transfusion in 25% of children undergoing cardiac operations. Compared with children who received a transfusion during the postoperative period, and a fortiori to those who received a transfusion intraoperatively, these patients had a shorter length of postoperative mechanical ventilation and a shorter PICU stay [34].…”
Section: Commentmentioning
confidence: 99%
“…There is an emerging body of evidence linking postoperative RBC transfusion to adverse clinical outcomes, and two randomized clinical trials published recently, as well as a subgroup analysis of the Transfusion Requirements in Pediatric Intensive Care Units study, suggested that the benefit of achieving high hemoglobin concentrations in cyanotic patients may be overstated [8,34,37]. In this context, there is enough equipoise to warrant the execution of a large randomized controlled trial on the question of perioperative RBC transfusion in children undergoing cardiac operations.…”
Section: Commentmentioning
confidence: 99%
“…The selection of risk factors as potential confounders influencing the outcome parameters is largely based on our recent analyses of pediatric patients treated with the same comprehensive blood-sparing approach [22]. The major general limitation of retrospective studies that only retrospectively available covariates can be included in the analyses also applies to this study [25].…”
Section: Discussionmentioning
confidence: 99%
“…This has been the policy in our institution for several years, although the supply of fresh RBCs is not invariably possible. In addition, a dedicated group of surgeons, anesthetists, and perfusionists apply a comprehensive blood-sparing approach to avoid or minimize the need for transfusion [19,20,21,22]. Here, we present results on pediatric patients who underwent open heart surgery and received RBCs from a single unit with a storage time ranging from 0 to 14 days.…”
Section: Introductionmentioning
confidence: 99%
“…At our institution, we have established a comprehensive blood-sparing approach which includes minimised CPB circuits with priming volumes of 95 and 110 mL for, respectively, infants <3 kg and 3 to 5 kg bodyweight and a transfusion trigger on CPB at 7 g/dL haemoglobin (Hb) concentration. [1][2][3] CPB circuits are primed with PRBCs only when the estimation based on bodyweight, preoperative haemoglobin concentration and priming volume predicts an haemoglobin concentration <7 g/dL. Thus, only in a minority is PRBC priming of the CPB circuit performed, but many, especially smaller infants, still require transfusion of PRBCs while on CPB, after weaning from CPB or during the further postoperative course.…”
Section: Introductionmentioning
confidence: 99%